Light‐Tunable 2D Esaki Diode Photodetector with Well‐Balanced High Detectivity and Response Speed. Issue 32 (3rd October 2022) - Li, Xuhong; Chen, Xiaoqing; Deng, Wenjie; Li, Songyu; Chu, Feihong; You, Congya; Li, Jingjie; Liu, Famin; Zhang, Yongzhe
Abstract: Van der Waals (vdW) heterojunctions composed of 2D layered materials exhibit novel physical phenomena that can power a range of electronic and photonic applications. Here, the first demonstration of the light switchable mechanism between the rectifier diode and Esaki diode in SnS2 /WSe2 ‐black phosphorus (BP) vdW heterojunctions is presented. In this design, the photogating effect of WSe2 ‐BP junction is employed as the switch toggle between rectifier diode and Esaki diode. Based on this light switchable mechanism, a super‐linear photocurrent‐power dependence is observed and a high‐performance photodetector with high detectivity (5.1 × 10 11 Jones) and rapid response speed (<112 us) is obtained. A feasible strategy for a well‐balanced photodetector with high detectivity and response speed in the vdW heterojunction is provided. Abstract : A light‐tunable tunneling mechanism photodetector through the photogating effect of black phosphorus induced localized holes in the SnS2 /WSe2 ‐BP heterojunction. Base on this light‐tunable mechanism, a super‐linear photocurrent‐power dependence is discovered. This work provides a feasible strategy for both the photon‐generated carriers high gain and the fast extraction in 2D van der Waals heterojunction.